Non-Traumatic Chronic Nasosinusitis Disorders: Clinical and Computed Tomodensitometric Aspects in Cotonou in Benin, West Africa - yekpe, HERMIONE PATRICIA FRIDA; Djivèdé, Akann; Alexis, Dos Santos; ADJADOHOUN, SONIA B M G; Brigitte, Gbaguidi; Kofi Mensa, Savi de Tovè; BIAOU, OLIVIER; Vicentia, Boco (My University, 2020)
Introduction: Damage to the nasal cavities and sinuses of the face concern many disciplines, especially the specialist in Otorhinolaryngology and Cervical-Facial Surgery (ENT-CFS), since most symptoms have little value to direct the patient towards a precise diagnosis, radiological exploration, including three-dimensional imaging, provides diagnostic, therapeutic and follow-up support. The aim is to study the clinical and computed tomography scan aspects of non-traumatic chronic nasosinusitis disorders at the Teaching University Hospital of Hubert Koutoukou Maga (CNHU/HKM) in Cotonou. Material and Method: It was a descriptive and analytical study with retrospective collection, carried out over a period of 36 months from January 1st, 2014 to December 31st, 2016; on 261 files of patients seen in Otorhinolaryngology (ENT) and Cervico Facial Surgery (CFS) consultating for a chronic nasosinusitis disorder with no trauma notion and having performed a CT scan. Results: Chronic lesions of the nasal sinus cavities accounted for 13.42% of ENT consultations. There was female predominance with a sex ratio of 0.85. The clinic varied, the most common signs were rhinorrhea (74%), headache (73.6%) and sneezing (38.3%). On computed tomography scan, 225 results were pathological. Sinus backfilling was in the lead with 66.7% followed by mucous thickening with 60.44%, and by bone involvement in 28%. Inflammatory pathologies (82.22%) were on top of the list, followed by do-tumoral pathologies (20.9%). The anterior sinus complex was the most affected (56%) with predominance of the maxillary sinuses. Conclusion: chronic nasosinusitis disorders are frequent in daily practice, with a varied clinic. Computed tomography scan is a major diagnostic tool that should be favored.
Keywords: Chronic Nasosinusitis Disorder; Computed Tomography; CNHU/HKM; Cotonou